An overview on the role of lanthanide series (rare earth metals) in H2 and syngas production from CH4 reforming processes - Sumaiya, Zainal Abidin; Osazuwa, Osarieme Uyi (Elsevier, 2020)
The activity of catalysts in reforming processes is greatly hindered by carbon deposition on their active sites. In this vein, a number of studies on catalyst behavior in CH4 reforming processes have been reviewed with focus on lanthanide series as catalyst, promoter and support to improve activity and eliminate carbon. Studies have shown that various catalyst combined with the lanthanide series have effectively removed carbon from active metals sites. Therefore, this study has provided a detailed review of several works on reforming processes that have applied lanthanide series as catalyst, promoter and support. Comparative data for various CH4 reforming processes using lanthanide series as catalyst material have been outlined. Data from this study can be applied industrially to synthesize a catalyst resistant to deactivation, hence, optimizing energy production and profit.